5α-Reductase Inhibitors Could Prevent the Clinical and Pathological Progression of Prostate Cancer: A Meta-analysis - Yang, Yue; Hu, Haifeng; Zhang, Hanchao; Liu, Zhengdao; Zhao, Faliang; Yang, Jin; Liang, Guobiao (Urology Journal, 2021)
Purpose: To explore the efficacy of 5-ARIs in PCA (Prostate Cancer). Methods: Searching through the major medical databases such as PubMed, Science Citation Index, EMBASE, Medline, Web of Science, Cochrane Library for all published studies in English until 2018. The following search terms were used: “Finasteride”, “dutasteride”, “5α reductase inhibitors”, “5-ARIs”, “prostate cancer”, “prostate neoplasm” and the additional related studies were manually searched. Newcastle-Ottawa Scale (NOS) assessed the qualities of studies, and the outcome measures were observed by RR or OR with 95% CIs. Results: We included 9 eligible studies for analyses from 2011 to 2017. We found that 5-ARIs group may have fewer progression (OR = 0.48 95%CI: 0.37-0.61 P < 0.00001, I2=4% p = 0.39) and lower pathological progression (OR = 0.46; 95%CI: 0.29-0.73; p = 0.001, I2=0% p = 0.45), compared with control groups. However, the OS did not show significant difference between two groups (OR=1.10; 95%CI:0.90-1.35; P = 0.35, I2 = 93% P < .00001 ). Conclusion: The use of 5-ARIs could prevent progression in PCA patients both clinical and pathological.